Sensitivity of larval Dendropsophus haddadi (Bastos and Pombal 1996), an anuran species from the Brazilian Atlantic Forest, to acute exposure to nitrate - Egea-Serrano, Andrés (Ecotoxicology (London, England), 2025)
© 2024. The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.